The levels of psyche and the archetype elements of Amy Loughren in The Good Nurse movie - Octavia Sylviana Dewi; Dyah Ambar Wuryandari (Lililacs Journal, 2024)
Archetype was an originates concept from psychology by Swiss psychiatrist Carl Gustav Jung. The researcher analyzed the levels of the psyche and the archetype elements based on Carl Jung’s theory in Amy Loughren as the main character of The Good Nurse movie. The objective of the research is to find out the levels of the psyche and the Archetype elements that appear in Amy Loughren in The Good Nurse movie based on Carl Gustav Jung’s theory. The researcher used qualitative descriptive method. The data were collected from dialogues in the movie. The researcher found the levels of the psyche are represented in Amy’s character with 3 data of Conscious (Ego). The researcher also found 7 Archetypes Elements that appeared, they were Persona (5 data), Shadow (2 data), Animus (1 datum), Great Mother (4 data), Wise Old Man (2 data), Hero (2 data) and Self (1 datum).